1997
DOI: 10.1111/j.1399-3011.1997.tb01208.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray structures of aza‐proline‐containing peptides

Abstract: The aza‐analogue of proline (AzPro) contains a nitrogen atom in place of the CHα of the cognate residue. The resolution of the crystal structures of seven AzPro‐containing peptides, presenting a set of ten AzPro motifs, reveals the structural properties of this particular aza‐residue. Because of sterical hindrances, both nitrogen atoms are out of planarity, and the reduced electronic conjugation in the two AzPro‐adjacent amide groups probably explains the longer amide bond distances and the weak proton‐accepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…These modied peptides showed a attening of the spatial arrangement of the substituents linked to the new nitrogen atom while having the potential to exhibit adaptive chirality. 22,23 This structural difference was also observed by us in the comparison between a DKP and its aza-DKP analogue by X-ray crystallography (Fig. 3).…”
Section: Introductionsupporting
confidence: 75%
“…These modied peptides showed a attening of the spatial arrangement of the substituents linked to the new nitrogen atom while having the potential to exhibit adaptive chirality. 22,23 This structural difference was also observed by us in the comparison between a DKP and its aza-DKP analogue by X-ray crystallography (Fig. 3).…”
Section: Introductionsupporting
confidence: 75%
“…This nitrogen substitution is believed to have little effect on the overall physicochemical profiles of these peptides; however, electronic repulsion between the adjacent nitrogen atoms has been suggested to induce type I and II b-turn conformations. [19][20][21][22][23][24][25][26][27][28][29][30][31] This b-turn geometry of aza amino acid-containing peptides may contribute to improve binding affinity of metastin analogs for KISS1R. NMR analysis of the metastin(45-54) analog in dodecylphosphocholine micelles showed that it contained several tight turn structures such as miscellaneous type IV b-turns (residues Asn 48 -Gly 51 and Gly 51 -Phe 54 ).…”
Section: Introductionmentioning
confidence: 98%
“…88,89 This replacement eliminates chirality at the a-position and decreases the electrophilicity of the carbonyl group by altering the geometry of the a position from tetrahedral to trigonal (i.e., planar, achiral), with dihedral angles (j = 901 AE 301 or À901 AE 301, and C = 01 AE 301 or 1801 AE 301) providing b-turn conformations. [90][91][92][93] b-Turn azapeptide conformations have been demonstrated by X-ray crystallography, [94][95][96] spectroscopy, 97,98 and by computational models 90,92,93 (Fig. 9).…”
Section: Azapeptidesmentioning
confidence: 99%